Biomechanical properties of acellular scar ECM during the acute to chronic stages of myocardial infarction. (April 2021) - Brazile, Bryn L.; Butler, J. Ryan; Patnaik, Sourav S.; Claude, Andrew; Prabhu, Raj; Williams, Lakiesha N.; Perez, Karla L.; Nguyen, Kytai T.; Zhang, Ge; Bajona, Pietro; Peltz, Matthias; Yang, Yong; et al.
Abstract: After myocardial infarction (MI), the infarcted tissue undergoes dynamic and time-dependent changes. Previous knowledge on MI biomechanical alterations has been obtained by studying the explanted scar tissues. In this study, we decellularized MI scar tissue and characterized the biomechanics of the obtained pure scar ECM. By thoroughly removing the cellular content in the MI scar tissue, we were able to avoid its confounding effects. Rat MI hearts were obtained from a reliable and reproducible model based on permanent left coronary artery ligation (PLCAL). MI heart explants at various time points (15 min, 1 week, 2 weeks, 4 weeks, and 12 weeks) were subjected to decellularization with 0.1% sodium dodecyl sulfate solution for ~1–2 weeks to obtain acellular scar ECM. A biaxial mechanical testing system was used to characterize the acellular scar ECM under physiologically relevant loading conditions. After decellularization, large decrease in wall thickness was observed in the native heart ECM and 15 min scar ECM, implying the collapse of cardiomyocyte lacunae after removal of heart muscle fibers. For scar ECM 1 week, 2 weeks, and 4 weeks post infarction, the decrease in wall thickness after decellularization was small. For scar ECM 12 weeks post infarction, the reduction amount of wall thickness due to decellularization was minimal. We found that the scar ECM preserved the overall mechanical anisotropy of the native ventricle wall and MI scar tissue, in which the longitudinal direction is more extensible. Acellular scar ECM from 15 min to 12 weeks post infarction showed an overall stiffening trend in biaxial behavior, in which longitudinal direction was mostly affected and manifested with a decreased extensibility and increased modulus. This reduction trend of longitudinal extensibility also led to a decreased anisotropy index in the scar ECM from the acute to chronic stages of MI. The post-MI change in biomechanical properties of the scar ECM reflected the alterations of collagen fiber network, confirmed by the histology of scar ECM. In short, the reported structure-property relationship reveals how scar ECM biophysical properties evolve from the acute to chronic stages of MI. The obtained information will help establish a knowledge basis about the dynamics of scar ECM to better understand post-MI cardiac remodeling.